Hot isostatic pressed pyrochlore glass‐ceramics: Revealing structure insides at the reaction interface. Issue 11 (6th July 2021) - Zhang, Yingjie; Wei, Tao; Xu, Alan; Dayal, Pranesh; Gregg, Daniel J.
Abstract: As potential waste forms for immobilizing actinide‐rich radioactive wastes, Eu2 Ti2 O7 (Eu as a surrogate for minor actinides) pyrochlore glass‐ceramics were fabricated via hot isostatic pressing (HIPing) at 1200°C. The structure and microstructure at the reaction interface between the glass‐ceramic waste form and the stainless steel (SS) canister under HIPing conditions were carefully investigated with scanning electron microscopy (SEM), transmission electron microscopy (TEM), and synchrotron single crystal X‐ray diffraction (SC‐XRD). The interactions at the reaction interface led to the formations of a ~10‐µm‐thick Cr2 O3 layer as the oxidation front of the SS and a layer of a mixed oxide phase (Eu1.25 SiCr0.8 Ti1.2 O7.5 ) on the glass‐ceramic side of the reaction interface. The crystal structure of such a unique mixed oxide phase was revealed indubitably with a combination of synchrotron SC‐XRD and TEM assisted with a focused ion beam (FIB) SEM system. The improved structural understanding of the reaction interface will help to support the utilization of HIPing as a versatile hot consolidation process for the treatment of radioactive wastes. Abstract : The structure insides at the reaction interface between Eu2 Ti2 O7 pyrochlore glass‐ceramics and the 304 L stainless steel canister under hot isostatic pressing conditions at 1200°C were revealed with a combination of scanning electron microscopy (SEM), transmission electron microscopy and synchrotron single crystal XRD assisted with the focused ion beam‐SEM sample preparations